A NEW SUBSPECIES OF APOLINAR’S WREN (CISTOTHORUS APOLINARI, AVES: TROGLODYTIDAE), AN ENDANGERED COLOMBIAN ENDEMIC - STILES F. GARY; CAYCEDO PAULA (Caldasia)
We describe Cistothorus apolinari hernandezi, subsp. nov. from wet páramo of the Sumapaz massif south of Bogotá, Colombia. This form differs from the nominate of the wetlands of the Cundinamarca-Boyacá Plateau in size, coloration, ecology, social structure and song and appears to be isolated from it by some 1000 m of elevation and different habitat preferences. A second population apparently occurs some 300 km further northeast in the Sierra Nevada del Cocuy in Dept. Boyacá but no data exist for intervening páramos. As a species, C. apolinari is critically endangered but the wetland and páramo populations face different threats and require different conservation strategies; distinguishing the latter population formally helps call attention to this situation.